¨ OTIMIZAÇÃO DAS CONDIÇÕES DO PROCESSO DE SECAGEM DA POLPA DO MAMÃO FORMOSA (Carica Papaya L.) EM LEITO DE ESPUMA E LEITO FIXO PARA PRODUÇÃO DE FARINHA - Peixoto, Emanuelly Zanotti Hoffman (2020)
Papaya (Carica papaya L.) is a very perishable fruit rich in antioxidant compounds. Its waste is high, generating economic losses and environmental losses. The objective of the present study was to optimize the drying processes in the foam bed and in the